Water distribution modelling of capillary absorption in cementitious materials. (20th August 2019) - Zhang, Jianchao; Hong, Shuxian; Dong, Biqin; Tang, Luping; Lin, Chen; Liu, Zhichao; Xing, Feng
Highlights: A novel capillary absorption model considered by tortuosity of capillary pores is proposed. Analytical model for water content distribution is established based on above model. The validity and applicability of the model are demonstrated by experimental results of XCT. Abstract: In this paper, a novel capillary absorption model is proposed to investigate the capillary absorption process of cementitious materials. This model mainly consider the influence of tortuosity of the capillary pores of cement paste, which is the key factor affecting the capillary absorption process. The proposed model is verified by the capillary absorption process of paste samples with different water/cement ratios. The absorption height and water content profile of testing samples are measured by X-ray computed tomography. The results show that the proposed capillary absorption model that takes the tortuosity of capillary pores into consideration is suitable for investigating the capillary absorption process of water in cementitious materials.